Syllinae (Syllidae: Polychaeta) from Australia. Part 4. The genus Haplosyllis Langerhans, 1879 - Lattig, Patricia; Martin, Daniel; San Martín, Guillermo (Zootaxa, 2010)
Large collections of Syllidae (Polychaeta) from around Australia housed at the Australian Museum (Sydney) have been examined and identified. Among them are seven known species of Haplosyllis Langerhans, 1879, which are here redescribed and figured: H. uncinigera (Grube, 1878), H. basticola Sardá, Paul & Ávila, 2002, H. crassicirrata Aguado, San Martín & Nishi, 2006, H. ingensicola Lattig, Martin & Aguado, 2010, H. tenhovei Lattig, Martin & Aguado, 2010, H. djiboutiensis Gravier, 1900 (the most widely distributed species) and H. cf. spongicola. The latter is morphologically very similar to the type series of H. spongicola (Grube, 1855) from the Mediterranean, so future molecular studies would be necessary to clarify its taxonomic status. In addition, H. imajimai sp. nov., H. sanchoi sp. nov., and H. sandii sp. nov., are newly described. All relevant characters for all species are fully illustrated, most of them using Scanning Electron Microscopy. Finally, a key to the Australian species is given.